Decision support systems III - impact of decision support systems for global environments : Euro Working Group Workshops, EWG-DSS 2013, Thessaloniki, Greece, May 29-31, 2013, and Rome, Italy, July 1-4, 2013, Revised Selected and Extended Papers - Hernandez, Jorge E.; Zarate, Pascale; Liu, Shaofeng; Ribeiro, Rita; Delibasic, Boris; Papathanasiou, Jason; Dargam, Fatima (Lecture Notes in Business Information Processing, 2014)
This book contains extended and revised versions of a set of selected papers from two workshops organized by the Euro Working Group on Decision Support Systems (EWG-DSS), which were held in Thessaloniki, Greece, and Rome, Italy, in May and July 2013. From a total of 45 submissions, 15 papers were accepted for publication in this edition after being reviewed by at least three internationally known experts from the EWG-DSS Program Committee and external invited reviewers. The selected papers are representative of current research activities in the area of operational research and decision support systems, focusing on topics such as decision making using social networks and Web resources; spatio-temporal Web-based decision making; group support systems; technical, legal, and social aspects of decision making; knowledge management and decision support systems; business intelligence and data warehousing; and negotiation support systems.